Parental care in the dwarf caiman, Paleosuchus palpebrosus Cuvier, 1807 (Reptilia: Crocodilia: Alligatoridae) - Campos, Zilca M.S.; Sanaiotti, Tânia Margarete; Muniz, Fábio L.; Farias, Izeni P.; Magnusson, William Ernest (Journal of Natural History, 2012)
Post-hatching parental care is common in crocodilians, but the little information available for Cuvier's dwarf caiman (Paleosuchus palpebrosus) indicates that they show little post-hatching parental care. During surveys undertaken between 2005 and 2011, we counted and captured groups of hatchlings and observed the presence or absence of attending adults in streams around the Pantanal, along the Guaporé-Madeira River and flooded forest in central Amazonia, Brazil. We found 37 groups of hatchlings, of which 29 were accompanied by adults. We captured 13 of these adults and all were females. The groups of hatchlings remained with adults for up to 21 months. We monitored females and hatchlings in streams around the Pantanal using captures and with radiotelemetry and showed that females and hatchlings frequently remained together in burrows, especially during the dry season. © 2012 Copyright Taylor and Francis Group, LLC.
Keywords: Adult; Burrow; Crocodilian; Floodplain Forest; Hatching; Maternal Care; Radio Telemetry; Seasonality; Stream; Amazonas; Madeira River; Pantanal; Alligatorinae; Caiman; Crocodylidae (all Crocodiles); Paleosuchus Palpebrosus; Reptilia